The impact of organizational climate on employee’s work passion and organizational commitment - P. Yukthamarani Permarupan; Roselina Ahmad Saufi; Raja Suzana Raja Kasim; Bamini KPD Balakrishnan (Elsevier, 2013)
This paper proposes to examine the organizational climate and employee’s work passion and organizational commitment within academician of public and private Universities in Malaysia. An argument is put forward that there is a causal link of good organizational climate, employees work passion and commitment in an organization. A conceptual model of organizational climate and employee’s work passion and organizational commitment is presented that provides an explanation of the linkage between these variables. A 500 sample of academicians from public and private Malaysian universities were administered using organizational climate questionnaire. This cross-sectional study aimed to address the employee’s needs and expectation from the employer in the aspect of organizational climate and commitment. Thus, by understanding the empirical results of the organizational climate, this findings will be able to emerge as an improvised model to enhance employee’s work passion as well as organizational commitment.